A Quality Assessment of Online Patient Information Regarding Rhinoplasty - Shamil, Eamon; Scenza, Gabriela Di; Ghani, Shahi Abdul; Fan, Ka Siu; Ragulan, Suthaharan; Salem, Joseph; Šurda, Pavol; D'Souza, Alwyn Ray (Facial Plastic Surgery, 2021)
There is a large demand for online patient information for patients considering rhinoplasty. While there are many resources available, the quality and content of the information provided are unknown. This study aimed to assess the quality of the most popular information available online, using the “Ensuring Quality Information for Patients” (EQIP) tool to evaluate the content, structure, and readability of patient information on websites. Search terms including nose operation, nose job, nose reshaping, nose tip surgery, rhinoplasty, septorhinoplasty, were identified using Google AdWords and Trends. Unique links from the first 10 pages for each term were identified and evaluated with websites written in English and for general non-medical public use were included. 295 websites met the eligibility criteria with a median overall EQIP score of 17. Only 33% contained balanced information on the risks and benefits. Bleeding and infection risk was only mentioned in 29% and 27% of websites, respectively. Two percent described complication rates of the procedures and only 20% of articles explained further surgery may be required to achieve patient cosmetic or functional satisfaction. Information regarding rhinoplasty available online is currently of poor quality. The lack of effective risk counselling, possible outcome management, and complications may likely lead to unrealistic expectations of rhinoplasty. It is crucial the risks of surgery are communicated to the patient to ensure they can make an informed decision. Improved education through online resources would likely help to promote more realistic patient expectations.
Keywords: rhinoplasty; online information; patient expectations